The effectiveness of Dragon Boat racing on body image and traumatic symptoms of breast cancer patients - Chiara Fioretti; Silvia Coppola; Sara Boscaino; Giovanna Celia; Rodolfo Vastola; Mauro Cozzolino (Health Psychology Research)
# Objective